# Use the identity

The given identity is (a+b) (a–b) = a2 –b2

(i) (x – 6) (x + 6)

Using the given identity

Here a = x and b = 6

= x2 – 62

= x2 – 36

(ii) (3x + 5)(3x + 5)

Using the given identity

Here a = 3x and b = 5

= (3x)2 – 52

= 9x2 – 25

(iii) (2a + 4b)(2a – 4b)

Using the given identity

Here a = 2a and b = 4b

= (2a)2 – (4b)2

= 4a2 – 16b2

(iv) Using the given identity

Here  = Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses RELATED QUESTIONS :

Find the product:Karnataka Board - Mathematics Part I

If a, b are ratioKarnataka Board - Mathematics Part I

Use the identity Karnataka Board - Mathematics Part I

Express the folloKarnataka Board - Mathematics Part I

Find the product:Karnataka Board - Mathematics Part I

Simplify:

Karnataka Board - Mathematics Part I

Find the product:Karnataka Board - Mathematics Part I

Find the product:Karnataka Board - Mathematics Part I

Evaluate these usKarnataka Board - Mathematics Part I

Find the product:Karnataka Board - Mathematics Part I